Uso de las plantas medicinales en el tratamiento de enfermedades respiratorias en niños de 5 a 10 años en El Recinto La Angela Cantón Baba. Provincia de Los Ríos. Junio-octubre 2023. - Alvarado Acosta, José Daniel (2023)
The research entitled use of medicinal plants in the treatment of respiratory diseases in children from 5 to 10 years old at the La Angela campus had the objective of determining the relationship between the use of medicinal plants and the treatment of respiratory diseases in children from 5 to 10 years old. 10 years in the La Ángela canton Baba facility. Province of the Rivers. June-October 2023. I have a correlational descriptive methodology, using as an instrument a self-developed questionnaire in a sample of 51 participants. The results are that 96.08% of people use medicinal plants for the treatment of respiratory diseases in children compared to 3.92% who mentioned that they do not use these plants. It was concluded that there is a positive correlation (Sig. 0.011) between the use of medicinal plants and the treatment of respiratory diseases in children from 5 to 10 years old.